Ameliorative effect of taurine-chloramine in azathioprine-induced testicular damage; a deeper insight into the mechanism of protection - Mona F. Schaalan; Basma K. Ramadan; Azza H. Abd Elwahab (BMC, 2018)
Abstract Background The male reproductive system is a sensitive and intricate process that can be distressed following exposure to various toxicants. Therapeutic drugs, especially chemotherapeutics, can also adversely affect male fertility by instigating hormonal changes leading to testicular cells injury. Azathioprine (AZA) is an effective anticancer drug, but some cases of testicular toxicity have been reported. The aim of this work was to investigate the protective effects of taurine chloramine (TAU-Cl), a reported antioxidant and antiinflammtory peptide, against AZA-induced testicular dysfunction in male rats and ascertain the contributing mechanisms. Methods Forty male rats were allocated into four equal groups; (i) normal control rats, (ii) TAU-Cl group (100 mg/kg b.w/day for 10 weeks, (iii) AZA group (5 mg/day for 4 weeks); (iv) TAU-Cl/AZA group. Results AZA caused increased DNA damage in the testes, and alterations in sex hormones and sperm quality, including sperm count, viability, and motility. Moreover, testicular tissue from the AZA-treated group had increased levels of oxidative stress indicator, MDA, and decreased activity of the antioxidant enzymes as superoxide dismutase (SOD), reduced glutathione (GSH) and catalase (CAT) levels. These deleterious events were accompanied by upregulated levels of the pro-inflammatory cytokines, tumor necrosis factor-alpha (TNF-α), and protein expression of iNOS and NFκB-p65, interleukin-1beta (IL-1β), and proapoptotic marker; caspase-9, together with decreased Bcl-2, NrF2 and hemeoxygenase (HO-1) expression. In contrast, TAU-Cl pretreatment significantly abrogated these toxic effects which were confirmed histologically. Conclusion Pretreatment with TAU-Cl exerts a protective effect against AZA-induced male reproductive testicular atrophy. This finding could open new avenues for the use of TAU-Cl as a complementary approach to chemotherapy supportive care.